PENGARUH DISKRIMINASI DAN PEMERIKSAAN PAJAK TERHADAP PERSEPSI WAJIB PAJAK ORANG PRIBADI MENGENAI PENGGELAPAN PAJAK DI KOTA BITUNG (Studi Kasus Pada WPOP yang ditemui di KPP Pratama Bitung) - Widjaja, Prielly Natasya Kartini; Lambey, Linda; Walandouw, Stanley Kho (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Tax is the highest revenue of the country that. Therefore, government continues to increase the source of revenue derived from taxes. However, in reality there are many taxpayers who do not obey tax laws by evading their taxes. Tax Evasion is a taxpayers act who always tries to minimize the tax payable by violating the provisions of tax laws. The purpose of this research is to find out the effect of tax discrimination and tax audit of tax evasion. Data were collected by questionnaires. Questionnaires were filled up by 100 tax payers in KPP Pratama Bitung. Technique sampling is non probability sampling with convenience sampling or accidental sampling method. This research used multiple linear regression method and SPSS software version 21.0 was utilized. The result shows tax discrimination has no effect on tax evasion and tax audit influence on tax evasion.Keywords: discrimination, tax audit, tax evasion.